2006
DOI: 10.1002/hup.766
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of simultaneous polysubstance use in drug using university students

Abstract: Simultaneous polysubstance use (SPU) is a common phenomenon, yet little is known about how various substances are used with one another. In the present study 149 drug-using university students completed structured interviews about their use of various substances. For each substance ever used, participants provided details about the type, order and amount of all substances co-administered during its most recent administration. Alcohol, tobacco and cannabis were frequently co-administered with each other and wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
178
1
13

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 243 publications
(206 citation statements)
references
References 42 publications
13
178
1
13
Order By: Relevance
“…2,9 However unlike previous research findings, the current results did not reveal any significant difference between simultaneous polydrug users and non-users in relation to academic performance, being victims of violent acts or involvement in any legal situations. 10 The findings also revealed that most of the undergraduate students sampled were studying full time and live with their families or other relatives in a family type setting.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…2,9 However unlike previous research findings, the current results did not reveal any significant difference between simultaneous polydrug users and non-users in relation to academic performance, being victims of violent acts or involvement in any legal situations. 10 The findings also revealed that most of the undergraduate students sampled were studying full time and live with their families or other relatives in a family type setting.…”
Section: Discussioncontrasting
confidence: 99%
“…Some of the items on the questionnaire were taken from pre-existing scales developed by other researchers. 1,[9][10][11][12] The questionnaire consisted of four sections with 58 closed ended questions which allowed respondents to provide additional information where necessary. Participants were included in the study after: 1) meeting specific inclusion and exclusion criteria; 2) agreeing after being given a verbal description of the study's goals, procedures, research informed consent form, and confidentiality assurance; 3) answers to any question participants may have on the study and data collection procedures; 4) signed the informed consent forms.…”
Section: Methodsmentioning
confidence: 99%
“…It is also notable that those in high-use groups were much more likely to be in a higher use group for other substances, a finding highly consistent with previous findings of simultaneous polysubstance use (Barrett et al, 2006). This suggests that high use of any class of drug represents increased risk for other forms of substance use.…”
Section: Discussionsupporting
confidence: 86%
“…8,[10][11] Actualmente en Colombia, no se dispone de información que referencie en específico la situación de policonsumo simultáneo de sustancias psicoactivas en estudiantes universitarios del área de la salud. El Estudio Nacional de Consumo de Sustancias Psicoactivas en Colombia, 2008 12 y la Encuesta Nacional sobre Consumo de Sustancias Psicoactivas en Jóvenes entre 10-24 años, 12 reportan como sustancias psicoactivas de mayor consumo, el alcohol y el tabaco.…”
Section: Discussionunclassified
“…La literatura hace referencia al uso de sustancias psicoactivas como alcohol, tabaco y marihuana, solas o combinadas, como factor de riesgo para la transición hacia el consumo de otras sustancias, como la cocaína, 10,[19][20][21] lo cual ha sido definido en otros estudios como "gateway model". 11 En este escenario de diversidad de sustancias psicoactivas y su policonsumo simultaneo, es necesario establecer las implicaciones para la salud humana, lo cual se sugiere profundizar a partir de los hallazgos de este estudio.…”
Section: Discussionunclassified